2006
DOI: 10.1021/ef050191x
|View full text |Cite
|
Sign up to set email alerts
|

Swelling of Nitrile Rubber by Selected Aromatics Blended in a Synthetic Jet Fuel

Abstract: To examine the contributions of different types of aromatics, the volume swell of nitrile rubber O-rings was determined in aromatic-free synthetic JP-5 fuel and in synthetic JP-5 fuel blended with selected aromatics. Additionally, partition coefficients between the O-ring and fuel phases were measured for the fuel and aromatic species. Volume swell was measured using an in situ optical dilatometry technique that provided temporal data, while partition coefficients were measured using direct thermal desorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 11 publications
0
81
0
Order By: Relevance
“…Fischer-Tropsch synthesis results in hydrocarbon molecules with no oxygen content, leading to excellent compatibility with existing engine and fueling infrastructure [37,94]. The lack of aromatic content in Fischer-Tropsch fuels can lead to issues associated with poor lubricity and seal-swell problems that must be overcome for it to be used within the current ground and air transportation fleets [36,[94][95][96]. Aromatic compounds, such as benzene or toluene, are hydrocarbon molecules that are stabilized by shared electrons within their carbon-ring structure, and are named as such due to their characteristic sweet smell.…”
Section: Advanced Biofuel Classificationmentioning
confidence: 99%
“…Fischer-Tropsch synthesis results in hydrocarbon molecules with no oxygen content, leading to excellent compatibility with existing engine and fueling infrastructure [37,94]. The lack of aromatic content in Fischer-Tropsch fuels can lead to issues associated with poor lubricity and seal-swell problems that must be overcome for it to be used within the current ground and air transportation fleets [36,[94][95][96]. Aromatic compounds, such as benzene or toluene, are hydrocarbon molecules that are stabilized by shared electrons within their carbon-ring structure, and are named as such due to their characteristic sweet smell.…”
Section: Advanced Biofuel Classificationmentioning
confidence: 99%
“…Research is being conducted to determine the minimum aromatic levels required to swell o-rings. 15,18 If additional research shows that a lower minimum percentage of aromatic content can adequately provide seal swell and other FFP characteristics, then the linear functional dependence will be used to maximize the percentage of FT while maintaining levels required for the proper function of fuel system materials. …”
Section: Aromatic Contentmentioning
confidence: 99%
“…Several studies have been performed to characterize the use of upgraded FT-derived fuels for aviation applications. [1][2][8][9][10][11][12][13][14][15][16][17][18][19] Studies with neat FT fuels have demonstrated that significant improvements in thermal oxidative stability and emission production can be realized while superior low-temperature properties can be achieved with a sufficiently high iso-alkane/n-alkane ratio. However, the IPK will not meet the JP-8 specification density requirement (minimum 0.775 g/mL) or potentially other specification and -Fit-for-Purpose‖ (FFP) properties.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer oxidation can be initiated when stabilizer additives are extracted during exposure to solvents, especially for B100. Indeed, the immersion of rubbers in solvents risks the extraction of fillers or additives (Richaud et al, 2013;Seehra et al, 2012;Graham et al, 2006;Trakarnpruk and Porntangjitlikit, 2008). The oxidation process eventually induces chain scission and decreases the polymer resistance to failure (Richaud et al, 2013).…”
Section: Discussionmentioning
confidence: 99%